Counterpoint: Prostate-specific antigen velocity is not of value for early detection of cancer - Vickers, Andrew J. (2013)
There is firm evidence that PSA velocity is statistically associated with many prostate cancer outcomes, including those related to early detection. But clinical use of a marker depends on clinical as well as statistical significance. Before using PSA velocity to inform decisions such as whether or not to biopsy a man, there should be clear evidence that doing so would improve clinical outcome. A systematic review on PSA velocity found that almost no studies had evaluated whether PSA velocity aids clinical decision-making. Since that time, several reports have indicated that including PSA in a statistical model alongside standard predictors (such as PSA and digital rectal exam) does not improve predictive accuracy. Specifically, biopsying men with high PSA velocity in the absence of other indications, as recommended by the NCCN guidelines, would lead to many millions of unnecessary biopsies, without a corresponding number of aggressive cancers being detected. Advocates of PSA velocity have been reduced to citing a single paper purporting to show that PSA velocity aids clinical decision-making. The paper involves selective reporting of an unusual subgroup analysis based on an extremely limited number of events. This is not to say that, in clinical practice, urologists should ignore prior PSA values: clinical judgment can be aided by careful longitudinal evaluation of PSA changes, interpreted in the context of symptoms and treatments. However, the literature clearly demonstrates that simplistic application of PSA velocity cut-offs is not of value for early detection of prostate cancer.